2020
DOI: 10.1136/bmjgh-2020-002425
|View full text |Cite
|
Sign up to set email alerts
|

Income security during periods of ill health: a scoping review of policies, practice and coverage in low-income and middle-income countries

Abstract: The COVID-19 pandemic is a reminder that insufficient income security in periods of ill health leads to economic hardship for individuals and hampers disease control efforts as people struggle to stay home when sick or advised to observe quarantine. Evidence on income security during periods of ill health is growing but has not previously been reviewed as a full body of work concerning low-income and middle-income countries (LMICs). We performed a scoping review to map the range, features, coverage, protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 103 publications
0
21
0
1
Order By: Relevance
“…BMJ Global Health remain over time, there is a growing consensus on the need to critically look at the future in terms of health, social and economic policy. [4][5][6] Fundamental changes are required in how we approach health and development objectives from the perspective of health and economic security, and on the basic principle of the guarantee of rights, protections and access to health, so that people and societies can be protected and survive in the face of multifaceted threats and risks-biological, natural or economic in nature.…”
Section: Summary Boxmentioning
confidence: 99%
“…BMJ Global Health remain over time, there is a growing consensus on the need to critically look at the future in terms of health, social and economic policy. [4][5][6] Fundamental changes are required in how we approach health and development objectives from the perspective of health and economic security, and on the basic principle of the guarantee of rights, protections and access to health, so that people and societies can be protected and survive in the face of multifaceted threats and risks-biological, natural or economic in nature.…”
Section: Summary Boxmentioning
confidence: 99%
“…A recent review article showed that, in most low and middle income countries, the effective coverage of the policies in place for income security is very low and existing schemes often exclude those who have the greatest need. 27 …”
Section: The Progressive Realisation Of Uhc Requires Good Governance mentioning
confidence: 99%
“…Many jobs have been, and will be, lost and companies and businesses may be unable to function efficiently due to sickness, isolation, quarantine, and various non-pharmaceutical community interventions including business closure, working from home, and physical distancing. 11 , 12 Provision of socioeconomic support is needed to remove possible disincentives and facilitate individual and public compliance with COVID-19 response measures. Furthermore, community confidence and compliance are more likely if there is reassurance that supply chains of food and medicines are resilient and that access is maintained for all.…”
mentioning
confidence: 99%